The effect of non-verbal communication between handball players on the effectiveness of offensive and defensive performance (Texas Journal of Multidisciplinary Studies, 2026)
The objective of this research is to design a training program based on non-verbal communication and to measure its effect on the effectiveness of offensive and defensive performance (individual and collective) among handball players. The researcher used the experimental method with a one-group design with pre and post-measurements. The research sample was chosen by the purposive method from handball players at Musayyib Sports Club, consisting of 15 players whose ages exceed 20 years, with an average age of 23.1 ± 1.5 years, and training experience of no less than 5 years. The training program based on non-verbal communication was applied for 12 weeks, with 3 training units per week, unit time 90 minutes. The researcher used observation cards to measure the effectiveness of offensive and defensive performance. The research results reached: the existence of statistically significant differences between the pre and postmeasurements in the indicators of attack effectiveness in favor of the post-measurement, and the existence of statistically significant differences between the pre and post-measurements in the indicators of defense effectiveness in favor of the post-measurement. The researcher recommended the necessity of including non-verbal communication drills within daily training units, using video feedback regularly, training defenders on reading the body language of attackers, developing specialized programs in non-verbal communication within coach preparation curricula, and conducting more studies on different age groups and sports.